Burkina Faso : Request for a Three-Year Arrangement Under the Extended Credit Facility; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2010)
Performance under the last ECF-supported program was broadly satisfactory. The government has prepared a medium-term policy framework to consolidate recent progress, and enhance growth prospects and poverty reduction efforts. Burkina Faso's risk of debt distress is high. Executive Directors suggest maintaining prudent borrowing policies. There are risks to the program, mostly linked to the economy's vulnerability to weather related and terms-of-trade shocks. Burkina Faso has a good track record of policy and reform implementation in areas critical for macroeconomic stability and growth.